A History of the Greek Letter General Fraternal Societies at the University of Wisconsin-La Crosse, 1909-75 - Slapak, Gregory D. (My University, 1975)
The purpose of this study was to investigate the history of, and present in a chronological order the development of the Greek Letter general fraternal societies on the University of Wisconsin - La Crosse campus. The order depicts the progression of evolution and change in the general fraternal system from the time of the La Crosse Normal School to the present at the University of Wisconsin - La Crosse. To further acquaint the reader with the national organizations to which the local chapters are affiliated, the author has also given a brief history of the national fraternities, as well as a descriptive list of all other forms of Greek organizations, existing on the present campus including; professionals, honoraries, and recognition Greekletter organizations on the La Crosse campus. As part of the above purpose, the study has a threefold specific purpose. 1) To trace historically the development of student participation in the general fraternal system at the University of Wisconsin-La Crosse. 2) To endeavor to show relationships between developmental trends within the university, the nation, and the general fraternal system. 3) To draw more general conclusions, and make some recommendations regarding the future development of student participation in the general fraternal system at the University of Wisconsin - La Crosse. The basic results of this study were: 1) A general fraternal system has existed on the La Crosse campus since 1910. 2) Since its organization in 1710, the general fraternal system has continually progressed except in times of national emergencies (World War I and World War II). 3) All present national general fraternities on campus with the exception of two, Delta Sigma Phi Fraternity and Phi Mu Sorority, had their origin from a local organization. 4) Greek organizations have played a continuous role in all major university-wide activities. 5) All general fraternal groups have served in both social and service capacities to their own organization, the university and the community. 6) Every general fraternal group is affiliated with either the National Interfraternity Conference or the National Panhellenic Conference. Because of their continued commitment to student development and their contributions in the university and community in the past, the author has faith that the general fraternal system, at the University of Wisconsin - La Crosse, will continue to strive along its existing path.
Keywords: Greek letter societies; University of Wisconsin-La Crosse -- Societies, etc. -- History